Taxonomic discrimination of evidence produced by pumas and dogs in outdoor depredations, from the forensic veterinary perspective taxonomic discrimination of evidence produced by pumas and dogs in outdoor depredations, from the forensic veterinary perspective - Scarso-Giaconi, F.; Fonseca, G. M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Puma (Puma concolor) has great adaptability,but the loss of habitat and prey has originated conflicts intheir interactions, which the predation of livestock hasoriginated misperception as pest and persecution. However,it has been shown that dogs (Canis lupus familiaris) canalso attack cattle causing disturbing damage. The lack ofstrategies and absence of qualified personnel evaluating eachcase can mask the real impact of the predation patterns ofpuma and dog attackes, that are different in their nature andeffects but could be misinterpreted causing excessive reactions.The interdisciplinary approach in a forensic contextcan optimize the information of the scene and the victim,and the veterinarian practioner have the knowledge andskills for this. The goal of this work is to review the state ofthe art of the analysis of evidence produced by pumas anddogs in outdoor depredations in forensic contexts and todiscuss future perspectives to improve this analysis withthe inclusion of forensic veterinarians in these procedures.